The environmental impact of crude oil formation water: a multivariate approach - Nnaji, C.C.; Agunwamba, J.C. (Химия и технология воды, 2013)
Water bodies receiving effluents from gas flow stations were sampled for ten months (March to December). Fifteen physicochemical parameters were monitored at six locations. Results obtained were analyzed unsing principal component analysis and cluster analysis. Five principal componets accounting for 72.43 % of total variance were isolated. The first pricncipal component was a measure of sea water intrusion, the second componet was a measure of total solids, the third component was a measure of organic pollution while the fourth and fifth principal component depicted the impact of effluent discharges. Effluents from gas flow stations were not the major causes of pollution of water resources in the locations of study. Cluster analysis showed no significant variation in the physicochemical characteristics of water samples based on location. Physicochemical parameters exhibited a seasonal pattern as a result of dilution by rainfall, reduced rate of evaporation in rainy season and dissolution of gaseous products of gas flaring in rain. Metals had no significant effect on the quality of water sampled from the six locations during the period of monitoring.